2015
DOI: 10.1002/ep.12097
|View full text |Cite
|
Sign up to set email alerts
|

Quantification, characterization, and anaerobic digestion of sheep manure: The influence of diet and addition of crude glycerin

Abstract: The objective of this study was to evaluate the influence of roughage-to-concentrate ratio on quantification and characterization of sheep manure, and to verify whether the addition of crude glycerin improves the efficiency of the anaerobic digestion process. The characterization study was carried out with two treatments (diet 1 with 40% roughage and 60% concentrate and diet 2 with 60% roughage and 40% concentrate) and 12 replicates per treatment. Parameters evaluated were as follows: production of manure, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…, respectively) ( Table 1 and Figure 2) were obtained by adding 52 and 64g waste cooking oil.kg manure -1 , respectively. These values are similar to the ones reported by ORRICO et al (2015) when studying co-digestion of swine manure and different levels of waste cooking oil inclusions. Those authors reported maximum yield of 263.6L biogas.kg VS added -1 when 6.08% oil were added, which justified recommending co-digestion.…”
Section: Specific Biogas Yieldsupporting
confidence: 89%
See 4 more Smart Citations
“…, respectively) ( Table 1 and Figure 2) were obtained by adding 52 and 64g waste cooking oil.kg manure -1 , respectively. These values are similar to the ones reported by ORRICO et al (2015) when studying co-digestion of swine manure and different levels of waste cooking oil inclusions. Those authors reported maximum yield of 263.6L biogas.kg VS added -1 when 6.08% oil were added, which justified recommending co-digestion.…”
Section: Specific Biogas Yieldsupporting
confidence: 89%
“…The inclusion of waste cooking oil provided sources of more readily degradable carbon than dietary fibers present in the diet of those animals, while fibers could be more easily digested after medium acidification since hemicellulose is more soluble in acid conditions (NEVES et al, 2009;OGEDA & PETRI, 2010). It is believed the ideal waste cooking oil inclusion levels (Table 1), which maximized reductions, complemented the characteristics of the substrates by providing sources of more easily degradable carbon, which enabled favorable nutrient concentrations for the process as observed by ORRICO et al (2015) when working with swine manure co-digestion and different levels of oil addition that research reported increases in COD, and; consequently, in carbon similar to those in the present study. Conversely, when the levels of waste cooking oil inclusion were exceeded, the process was hampered with decreased reduction values of these constituents.…”
Section: Reductions Of Solid and Fiber Constituentssupporting
confidence: 76%
See 3 more Smart Citations